The ossified hyoid apparatus of man in Peru - Palma, Ricardo (1955)
The total ossification of the elements forming the hyoid bone chain of elements connecting the hyoid bone to the base of cráneao is rare because not many anatomical museums in both Europe and America, exhibiting in their windows one exemplary.